PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY, EARNING PER SHARE DAN DIVIDEND PAYOUT RATIO TERHADAP PRICE EARNING RATIO (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Kimia Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017) - Cecep Ridwan; Astrid Dita Meiriana Hakim (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of debt to equity ratio, return on equity, earnings per share and dividend payout ratio on price earning ratio. The population in this study are chemical manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017 with a sample of 8 companies selected by the purposive sampling method. This study uses secondary data and panel data regression analysis techniques which are then processed using the Econometric Views 9 program and Microsoft Excel 2010. The results of this study indicate that there is a significant effect between earnings per share and dividend payout ratio on prices. Earning ratio, while debt to equity ratio and return on equity have no effect on price earning ratio.